Initial nucleation of Au on the (root2 x root2) R45 circle reconstructed Fe3O4 (001) surface - SHVETS, IGOR; MURPHY, SHANE (My University, 2006)
The initial nucleation of Au onto the (root 2 x root 2-)R45 degrees reconstructed Fe3O4(001) surface has been studied using scanning tunnelling microscopy. Au clusters are formed, with a typical lateral dimension of similar to 0.9 nm. The measured corrugation height of the clusters, similar to 0.1 nm, suggests that they are a single atomic layer in height. The clusters nucleate on a specific surface site, which lies at the centre of a (root 2 x root 2)R45 degrees reconstructed unit cell. The size and spatial distribution of the An clusters formed is shown to strongly correlate to the symmetry and periodicity of the reconstructed magnetite surface. It is also shown that even when the clusters are in close proximity they still only occupy this single nucleation site, and thus maintain the periodicity of the substrate. We relate the order and stability of this system to the fact that magnetite (001) is polar, and suggest that such surfaces offer ideal templates for self-assembly due to the stability of their polarity induced reconstructions.
PUBLISHED
Keywords: STM; oxide; surface; polar surface; self-assembly; clusters; Atomic, molecular and chemical physics